HIRING VETERANS : HOW TO LEVERAGE MILITARY TALENT FOR ORGANIZATIONAL GROWTH - Louis, Matthew J. (Career Press, 2023)
"A practical guide for prospective employers who want to hire veterans. It addresses this primary question: How can employers better prepare for and employ transitioning service members to improve the productivity and competitiveness of their organizations?"--